(untitled) (Research, Society and Development, 2021)
Introduction: The prevalence of pressure injury cases is exorbitant, and the prevention of PPLs remains a great challenge for nurses, and its incidence is considered an indicator of poor quality of care. Objectives: However, the aim of the study was to prepare an educational booklet emphasizing preventive measures for pressure injuries in bedridden patients. Methodology: This is a qualitative bibliographic research in which an educational booklet for bedridden patients was proposed. However, the methodological approach used will address bibliographic research as a reference for carrying out the same. To achieve the proposed objectives, a search was carried out in the database, Google Academic; VHL (Virtual Health Library), SCIELO (Scientific Electronic Library Online), PubMed; LILACS (Latin American and Caribbean Literature on Health Sciences). results and discussion: The material presented and developed for patient education was appointed through an educational booklet. The health education material must be written in a simple way, with a lower level of reading and allowing accurate information to be conveyed. Illustrations must be attractive with clear communication of their purpose. In addition, the images must reach a high level of attention and interest in reading the material, with changes in the population at different levels of education. Conclusion: The encouragement of self-care with prevention minimizes the morbidity and mortality rates related to infections in patients with LPP, reduces health expenses and improves the quality of life of patients with LPP.